Event Marketing Management and City Competitiveness: Mediation of Bandung City Branding - Ahmad Roni (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze the effect of Event Marketing Management on City Competitiveness with City Branding as a mediating variable in Bandung City. This research addresses the strategic role of event-based activities in strengthening city identity and enhancing competitiveness in an increasingly competitive urban environment. Research Methodology: This study used a quantitative approach with PLS-SEM. Data were collected through questionnaires from respondents experienced with Bandung City events and analyzed using SmartPLS 4.0 with bootstrapping to evaluate the measurement and structural models. Results: Event Marketing Management positively and significantly affects City Branding but has no significant direct effect on City Competitiveness. City Branding positively affects City Competitiveness and fully mediates the relationship between Event Marketing Management and City Competitiveness, indicating that events alone cannot enhance competitiveness without a coherent city branding strategy. Conclusions: The study concludes that City Branding plays a crucial role in transforming event marketing initiatives into sustainable city competitiveness. Limitations: This study was limited to Bandung City and used cross-sectional data, which may limit the generalizability of the results. Contributions: This study contributes to the urban marketing literature by empirically confirming the full mediating role of City Branding in the relationship between Event Marketing Management and City Competitiveness.